Comprehensive Treatment of Inflammatory Changes in Periodontal Tissues of Children Residing in Ecologically Polluted Areas of the Prykarpattia Region - Pavlyshyn, Мар’яна (Actual Dentistry, 2026)
Background. Chronic catarrhal gingivitis (CCG) in children is significantly influenced by environmental pollution, psychoemotional stress, as well as functional respiratory and swallowing disorders. These adverse factors contribute to persistent inflammation and the deterioration of oral hygiene. Objective. To evaluate the clinical effectiveness of a comprehensive therapy protocol — encompassing professional oral hygiene, localized treatment, and labial-myofunctional rehabilitation using the Froggy Mouth appliance — on the periodontal status, breathing type, and normalization of swallowing function in children residing in ecologically unfavorable conditions. Materials and Methods. The study sample comprised 120 adolescents aged 12–15 years with chronic catarrhal gingivitis, who were randomized into four groups based on environmental factors and the applied therapeutic protocol. The diagnostic complex included the monitoring of respiratory parameters, evaluation of the swallowing process, dynamic cytomorphometric assessment of the periodontium, and rheographic measurements. Following adenoidectomy, the patients underwent a course of myofunctional correction using the Froggy Mouth appliance combined with differentiated localized pharmacotherapy. Results. Children residing in ecologically unfavorable zones exhibited higher levels of psychoemotional stress, poorer oral hygiene, and more pronounced cytomorphometric markers of periodontal inflammation. Functional respiratory disorders and atypical swallowing were closely associated with types II and IV occlusal patterns. The comprehensive therapy protocol ensured a progressive normalization of cytomorphometric parameters and the restoration of swallowing function within 20–25 weeks. Conclusions. CCG in children is exacerbated by stress and adverse environmental factors. Effective management requires a multidisciplinary approach that integrates dental, otolaryngological (ENT), and myofunctional interventions. The Froggy Mouth appliance has demonstrated high efficacy in restoring swallowing function and improving periodontal status in high-risk patient groups.